Enhancing the Removal of Highly Concentrated CO2 Through Synergism between Microalgae Consortium and Nutrient Ratio in Photobioreactor (Indonesian Society for microbiology, 2016)
This research was carried out by developing the carbon capture and storage (CCS) technology to determine the synergism between microalgae consortium and the optimum nutrient ratio as an effort to obtain higher CO2 removal efficiency and CO2 utilization efficiency. The microalgae consortium consisting of Chlorella sp., Scenedesmus sp. and Ankistrodesmus sp. have been selected previously as potential candidates for Microbial Carbon Capture and Storage (MCCS) agent and already cultured continuously in PHM (Provasoli Haematococcus Media) artificial medium, in vertical column photobioreactor. Pure CO2 gas at a high concentration of 10% (v/v) flowed from the bottom of vertical column photobioreactor continuously with optimum flow rate of 5 L.min-1. A growth medium (PHM) containing artificial nutrients was flowed continuously at flow rate 7L.day-1 and detention time 3.8 days. Four fluorescent lamps were positioned outside the photo-bioreactor to obtain light intensity of 4000 lux, set for 16 hours light exposure and 8 hours dark, with operating temperature 30°C maintained during the study. Three compositional variations of microalgae consortium were used. They are as follows; Ch : Sc : An = 1: 1: 1; Ch : Sc = 1: 1; and Ch : An = 1: 1, where Ch, Sc, and An were Chlorella sp., Scenedesmus obliquus and Ankistrodesmus sp., respectively. The following variations of nutrient composition were used; C: N: P = 100: 10: 1, C: N: P = 100: 50: 1 and C: N: P = 100: 25: 1. The C, N, and P sources were CO2 (inorganic), KNO3, and KH2PO4, respectively. This study proves that synergism between the types making up the consortium also determined the ability to utilize inorganic carbon source. Without the presence of Ankistrodesmus sp., synergism between Scenedesmus obliquus and Chlorella sp. showed twice higher CO2 utilization efficiency in comparison to the synergism between Ankistrodesmus sp and Chlorella sp. Increased nitrogen concentration in medium increased the growth of Chlorella sp and Scenedesmus obliquus as a consortium, the CO2 removal efficiency, the CO2 utilization efficiency and the Carbon Uptake Rate. The nutrient ratios C:N:P of 100:50:1 could increase CO2 utilization efficiency upto 50% higher than the C:N:P of 100:10:1.